Big fishes in a big pond: a comparison between foreign and Chinese academics’ research influence in mainland China - Marini, G; Xu, X (SAGE Publications, 2023)
This article investigates the research influence (as indicated by citations and the SCImago quartile classification of target journal of publication) as per Global Western standards of foreign and Chinese academics in mainland China. The focus on research influence echoes the policy shifts in Chinese research from quantity to quality. This study analyses Scopus publications by foreign academics working in 15 research-intensive Chinese universities, comparing them with publications by Chinese colleagues in the same meso-institutional level (departments, schools, institutes) with same sex and academic rank, but with a doctoral degree attained in China. Findings show that foreign academics’ publications attract more citations, and, once checking by covariates, they are also more likely to publish in first quartile Scimago journals. Chinese academics’ publications, in comparison, tend to be in journals with higher Scimago quartile ranks on average. The study also reveals that foreign academics have more international co-authorships than their Chinese counterparts, despite this latter point being not necessarily conducive of more influent research.